Microbiological Trends and Antibiotic Susceptibility Patterns in Patients with Periprosthetic Joint Infection of the Hip or Knee over 6 Years - Frank Sebastian Fröschen; Thomas Martin Randau; Alexander Franz; Ernst Molitor; Achim Hoerauf; Gunnar Thorben Rembert Hischebeth (MDPI AG, 2022)
We sought to analyze trends of the causative pathogens and their antibiotic susceptibility patterns in patients with periprosthetic joint infections (PJI) of the hip and knee to get better insights and improve treatment. Retrospective evaluation of all consecutive patients with microbiological detection of a causative pathogen at a tertiary endoprothetic referral center between January 2016 and December 2021 in Germany was performed. Overall, 612 different microorganisms could be detected in 493 patients (hip: n = 293; knee: n = 200). Evaluation did not show a change in the relative abundance of pathogens detected, with coagulase-negative staphylococci (n = 275; 44.9%) found frequently, followed by S. aureus (n = 86; 14.1%), Enterococcus species (n = 57; 9.3%), Streptococcus species (n = 48; 7.8%), and Gram-negative bacteria (n = 80; 13.1%). Evaluation of the antibiotic susceptibilities showed increasing rates of oxacillin-resistant coagulase-negative staphylococci (60.4%; 46.8-76.7%) and piperacillin-tazobactam-resistant Gram-negative bacteria (26.5%; 0-57.1%), although statistically not significant. Resistance of Gram-positive bacteria to vancomycin (<1%) and Gram-negative microorganisms to meropenem (1.25%) remained an exception. In summary, coagulase-negative staphylococci, as the most frequent pathogen, displayed a continuously high rate of oxacillin resistance. For the highest antimicrobial coverage in the case of an empiric therapy/unknown pathogen, vancomycin might be chosen. Level of evidence: IV.